"It Isn't True that England Is the Moon": Comparative Constitutional Law as a Means of Constitutional Interpretation by the Courts?. Issue 2 (1st March 2017) - Kaiser, Anna-Bettina
Abstract : This Article evaluates the merits and problems of comparative constitutional law as an interpretive means by the courts. It pleas for a nuanced perspective towards both agents and methods of comparative constitutional law. The Article is in favor of the use of comparative constitutional law by the courts. However, challenges as to the legitimation of comparison in court, functional limits of comparative constitutional law in the judiciary, and methodological questions remain to be solved. As far as constitutional and supreme courts are concerned, this Article argues that arguments derived from comparison should be regarded as a means of persuasive reasoning.